Monitoring the Difference in Electrical Energy Between Communal Houses and Substations with Remote Communication Technology and the Internet of Things - Hidayat, Fahrizal Mufti; Marpaung, Jannus; Abidin, Zainal (Faculty of Engineering, Universitas Tanjungpura, 2025)
Electrical energy distribution systems are essential for modern life, especially in communal homes that use energy significantly. Monitoring and measuring the difference in electrical energy between pole substations and communal houses is important for cost efficiency and environmental sustainability to avoid misunderstandings between customers and electrical energy providers. Therefore, remote communication technology and the Internet of Things allow in real-time and accurate monitoring. In this study, the stages of collecting electricity parameters were carried out. The method of observing electrical power uses a current sensor (SCT-013) and a voltage sensor (ZMPT101B). The ESP32 microcontroller is used in measurement systems and as a link to the internet connection via a Wi-Fi network. The measurement data is stored in the data logger with txt format. The Internet of Things media platform used is a website-based Thinger.io. The test results show that long-distance energy difference monitiring can be done and send the parameters of voltage, current, power and energy in the form of kWh by Tx_1, Tx_2, Tx_3 and Rx to the thinger.io with periods every 5 seconds alternately. Then data was taken and the value for the total current was 5.66 A, the total power value was 1077.66 W, the energy value at the source was 10.78 kWh, so that the energy difference value from the three transmitters and the source was 0.18 kWh with an error value in the energy difference of 1.704%.